Glass for glass spacer for magnetic recording medium substrate or magnetic recording / reproducing device, magnetic recording medium substrate, magnetic recording medium, glass spacer for magnetic recording / reproducing device, and magnetic recording / reproducing device
By using amorphous glass with a higher elastic modulus as the magnetic recording medium substrate, the problem of vibration during high-speed rotation is solved, and a more stable magnetic recording medium and a higher storage density are achieved.
Patent Information
- Application Number
- CN202380063968.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing magnetic recording medium substrate is prone to vibrate when rotating at high speed, causing the magnetic head to collide with the surface of the magnetic recording medium, causing the magnetic head to scratch.
Amorphous glass with a higher elastic modulus is used as a magnetic recording medium substrate, and the rigidity and thermal stability of the glass are improved by adjusting the content of the chemical composition of the glass, such as B2O3, Na2O, CaO, MgO, etc.
It is realized that the vibration of the magnetic recording medium substrate is reduced during high-speed rotation, the risk of collision between the magnetic head and the surface of the magnetic recording medium is reduced, and the stability and storage density of the magnetic recording medium are improved.
Smart Images

Figure BDA0005298259770000211 
Figure BDA0005298259770000221 
Figure BDA0005298259770000231
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims the priority of PCT / JP2022 / 033744 filed on September 8, 2022, the entire contents of which are incorporated herein as special disclosures. Technical Field
[0003] The present invention relates to glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, a magnetic recording medium substrate, a magnetic recording medium, a glass spacer for a magnetic recording and reproducing device, and a magnetic recording and reproducing device. Background Art
[0004] As a substrate (magnetic recording medium substrate) for magnetic recording media such as hard disks, a substrate made of aluminum alloy has been used in the past. However, it has been pointed out that aluminum alloy substrates are prone to deformation. Therefore, currently, a magnetic recording medium substrate made of glass is widely used (for example, with reference to Japanese Patent Publication No. 2002-358626 (all of which are incorporated herein as special disclosures)). Summary of the invention
[0005] Glass for magnetic recording medium substrates is desired to have high rigidity for the following reasons.
[0006] Magnetic recording media are usually mounted inside hard disk drives (HDDs) assembled in devices such as personal computers. Inside the HDD, more than two magnetic recording media (disks) are mounted on the rotating shaft of the spindle motor, and data is written to or read from the magnetic recording layer of the magnetic recording media rotating at high speed inside the HDD by an actuator mounted on the HDD. When the magnetic recording medium rotates at high speed in order to write and read such data, the magnetic recording medium will vibrate violently, which may cause the magnetic head to collide with the surface of the magnetic recording medium, becoming the cause of the magnetic head scratching. With regard to HDD, the recording capacity can be increased by thinning the thickness of each magnetic recording medium and carrying more magnetic recording media in the HDD. However, the thinner the substrate is, the more likely the magnetic recording medium is to vibrate easily when rotating at high speed. In order to suppress this vibration, as a glass substrate for the magnetic recording medium, it is preferred to use a glass substrate with high rigidity that is not easy to vibrate when rotating at high speed even if it is thinned. As an index of this rigidity, for example, specific elastic modulus can be cited.
[0007] In view of the above circumstances, an object of one embodiment of the present invention is to provide a glass for a magnetic recording medium substrate having high rigidity. In one embodiment, an object of the present invention is to provide a glass for a magnetic recording medium substrate having a high specific elastic modulus.
[0008] One embodiment of the present invention is as follows.
[0009] [1] A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device (hereinafter referred to as "glass A"), which is an amorphous glass as follows:
[0010] The B2O3 content is 0.10 mol% or more and 2.00 mol% or less,
[0011] The Na2O content is 1.00 mol% or more and 6.00 mol% or less,
[0012] The CaO content is 0 mol% or more and 1.00 mol% or less,
[0013] The MgO content is 14.00 mol % or more.
[0014] [2] A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device (hereinafter referred to as "glass B"), which is an amorphous glass as follows:
[0015] The B2O3 content is 0.10 mol% or more and 2.00 mol% or less,
[0016] The Na2O content is 1.00 mol% or more and 6.00 mol% or less,
[0017] The CaO content is 0 mol% or more and 1.00 mol% or less,
[0018] The total content of MgO, SrO, CaO and BaO (MgO+SrO+CaO+BaO) is 14.00 mol% or more.
[0019] [3] The glass according to [1] or [2], wherein the molar ratio of the Na2O content to the total content of Li2O, Na2O and K2O (Na2O / (Li2O+Na2O+K2O)) is 0.950 or more.
[0020] [4] The glass according to any one of [1] to [3], which does not contain Li2O and K2O.
[0021] [5] The glass as described in any one of [1] to [4], wherein the total content of SiO2, B2O3 and Al2O3 (SiO2+B2O3+Al2O3) is 70 mol% or more.
[0022] [6] The glass as described in any one of [1] to [5], wherein the total content of SiO2 and B2O3 (SiO2+B2O3) is 58 mol% or more.
[0023] [7] The glass as described in any one of [1] to [6], wherein the total content of SiO2 and Al2O3 (SiO2+Al2O3) is 70 mol% or more.
[0024] [8] The glass described in [1] or [2], wherein the molar ratio of the Na2O content to the total content of Li2O, Na2O and K2O (Na2O / (Li2O+Na2O+K2O)) is 0.350 or more.
[0025] [9] The glass described in [1], [2] or [8], which contains Li2O.
[0026]
[10] Glass as described in [1], [2], [8] or [9], wherein the molar ratio of the Li2O content to the total content of Li2O, Na2O and K2O (Li2O / (Li2O+Na2O+K2O)) is less than 0.600.
[0027]
[11] The glass described in any one of [1], [2] and [8] to
[10] , wherein the molar ratio of SiO2 content to Na2O content (SiO2 / Na2O) is less than 50.0.
[0028]
[12] The glass according to any one of [1] to [7], wherein the molar ratio of the Na 2 O content to the MgO content (Na 2 O / MgO) exceeds 0.080.
[0029]
[13] The glass as described in any one of [1] to
[12] , wherein the TiO2 content is 4.00 mol% or less.
[0030]
[14] The glass according to any one of [1] to
[13] , wherein the ZnO content is 10.00 mol % or less.
[0031]
[15] The glass according to any one of [1] to
[14] , which has a specific elastic modulus of 35.0 MNm / kg or more.
[0032]
[16] The glass according to any one of [1] to
[15] , which has a glass transition temperature of 700° C. or higher.
[0033]
[17] A magnetic recording medium substrate comprising the glass according to any one of [1] to
[16] .
[0034]
[18] A magnetic recording medium comprising the magnetic recording medium substrate according to
[17] and a magnetic recording layer.
[0035]
[19] A glass spacer for a magnetic recording and reproducing device, comprising the glass described in any one of [1] to
[16] .
[0036]
[20] A magnetic recording and reproducing device comprising one or more selected from the group consisting of the magnetic recording medium described in
[18] and the glass spacer for a magnetic recording and reproducing device described in
[19] .
[0037] According to one embodiment of the present invention, a glass having high rigidity for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device can be provided. In addition, according to one embodiment, a magnetic recording medium substrate composed of the above-mentioned glass and a magnetic recording medium containing the substrate can also be provided. Furthermore, according to one embodiment, a glass spacer for a magnetic recording device composed of the above-mentioned glass can be provided. Further, according to one embodiment, a magnetic recording and reproducing device can be provided. DETAILED DESCRIPTION
[0038] [Glass]
[0039] Hereinafter, glass A and glass B are also referred to as "glass" in a unified manner. In addition, in the following description, unless otherwise specified, the description of glass A may also be applied to glass B, and the description of glass B may also be applied to glass A. Glass A and glass B are glasses for magnetic recording medium substrates or glass spacers for magnetic recording and reproducing devices, and are amorphous glasses. Amorphous glass is different from crystallized glass, and in fact does not contain a crystalline phase, but is a glass that shows a glass transition phenomenon by heating. On the other hand, the manufacturing process of crystallized glass is complicated. In addition, it is not easy to achieve the high smoothness required by the magnetic recording medium substrate by crystallized glass.
[0040] In addition, glass A and glass B may be amorphous oxide glasses. Oxide glasses are glasses whose main network-forming components are oxides.
[0041] The above-mentioned glass will be described in more detail below.
[0042] In the present invention and this specification, the glass composition is expressed as the glass composition based on oxides. Here, the "glass composition based on oxides" refers to the glass composition obtained by converting the material that is completely decomposed when the glass raw material is melted and exists in the form of oxides in the glass. In addition, unless otherwise specified, the glass composition is expressed on a molar basis (molar % or molar ratio).
[0043] The glass composition in the present invention and this specification can be obtained by methods such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Quantitative analysis is performed on each element separately using ICP-AES. Thereafter, the analysis value is converted into oxide expression. The analysis value based on ICP-AES sometimes contains a measurement error of, for example, about ±5% of the analysis value. Therefore, the value expressed by the oxide converted from the analysis value sometimes also contains an error of about ±5% in the same manner.
[0044] In addition, in the present invention and this specification, the content of a constituent component of 0%, 0.0%, 0.00%, or not contained or not introduced means that the constituent component is substantially not contained, and means that the content of the constituent component is below the level of impurities. Below the level of impurities means, for example, less than 0.01%.
[0045] <Glass Composition>
[0046] From the perspective of improving chemical durability and rigidity, the B2O3 content of the above-mentioned glass is less than 2.00%, preferably less than 1.80%, and more preferably less than 1.50%, less than 1.20%, less than 1.00%, less than 0.80%, less than 0.70%, less than 0.60%, less than 0.50%, and less than 0.40%. Glass with high chemical durability is not easy to produce surface roughness during grinding, cleaning, etc. due to its high acid resistance and / or alkali resistance, and it is easy to achieve low roughness of the glass surface, so it is preferred. Hereinafter, the performance of easy to achieve low roughening based on grinding is referred to as low roughening grinding performance. From the perspective of improved impact resistance, solubility and thermal stability, the B2O3 content of the above-mentioned glass is more than 0.10%, preferably more than 0.20%. Glass with high impact resistance is not easy to crack or collapse during cutting, grinding and other processing, so it is preferred. In addition, glass with high thermal stability is not easy to produce devitrification, so it is preferred.
[0047] In one embodiment, the glass may include one or both of SiO 2 and Al 2 O 3 .
[0048] From the aspect of improving chemical durability, the SiO2 content of the above-mentioned glass is preferably 50.00% or more, and more preferably 51.00% or more, 52.00% or more, 53.00% or more, 54.00% or more, 55.00% or more, 56.00% or more, 57.00% or more, 58.00% or more, 59.00% or more, 60.00% or more, 61.00% or more, 62.00% or more, 63.00% or more, and 64.00% or more. Glass with high chemical durability is not easy to produce surface roughness during grinding and cleaning, so it is preferred. On the other hand, from the perspective of further improving the rigidity, the SiO2 content is preferably less than 75.00%, and is further preferably less than 74.00%, less than 73.0%, less than 72.0%, less than 71.0%, less than 70.0%, less than 69.0%, less than 68.0%, less than 67.0%, less than 66.0%, less than 65.00%, less than 64.00%, less than 63.00%, less than 62.00%, and less than 61.00%.
[0049] From the perspective of improving thermal stability, the Al2O3 content of the above-mentioned glass is preferably 20.00% or less, and more preferably 19.00% or less, 18.00% or less, 17.00% or less, and 16.00% or less. In addition, from the perspective of maintaining the temperature required for melting the glass within an appropriate range, it is also preferred that the Al2O3 content is within the above range. On the other hand, from the perspective of further improving rigidity, the Al2O3 content is preferably 10.00% or more, and more preferably 11.00% or more, 12.00% or more, and 13.00% or more.
[0050] In the above-mentioned glass, from the perspective of improving the thermal stability of the glass, the total content of SiO2, B2O3 and Al2O3 (SiO2+B2O3+Al2O3) is preferably above 70.00%, and more preferably above 71.00%, above 72.00%, above 73.00%, above 74.00%, above 75.00%, above 76.00%, above 77.00%, above 78.00%, and above 79.00%, respectively. From the perspective of further improving solubility, the total content of SiO2, B2O3 and Al2O3 (SiO2+B2O3+Al2O3) of the above-mentioned glass is preferably less than 85.00%, and more preferably less than 84.00%, less than 83.00%, less than 82.00%, less than 81.00%, less than 80.00%, less than 79.00%, less than 78.00%, less than 77.00%, less than 76.00%, less than 75.00% and less than 74.00%, respectively.
[0051] From the perspective of improving the thermal stability of the glass, the total content of SiO2 and B2O3 (SiO2+B2O3) is preferably above 58.00%, and more preferably above 59.00%, above 60.00%, above 61.00%, above 62.00%, above 63.00%, and above 64.00%, respectively. From the perspective of further improving rigidity, the total content of SiO2 and B2O3 (SiO2+B2O3) of the above-mentioned glass is preferably less than 77.00%, and more preferably less than 76.00%, less than 75.00%, less than 74.00%, less than 73.00%, less than 72.00%, less than 71.00%, less than 70.00%, less than 69.00%, less than 68.00%, less than 67.00%, less than 66.00%, less than 65.00%, less than 64.00%, less than 63.00%, and less than 62.00%.
[0052] In the above-mentioned glass, from the aspect of chemical durability such as acid resistance and alkali resistance, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is preferably above 70.00%, and more preferably above 71.00%, above 72.00%, above 73.00%, above 74.00%, above 75.00%, above 76.00%, above 77.00%, above 78.00%, and above 79.00%, respectively. In addition, from the perspective of the solubility of the glass, the total content of SiO2 and Al2O3 (SiO2+Al2O3) of the above-mentioned glass is preferably less than 85.00%, and more preferably less than 84.00%, less than 83.00%, less than 82.00%, less than 81.00%, less than 80.00%, less than 79.00%, less than 78.00%, less than 77.00%, less than 76.00%, less than 75.00%, and less than 74.00%, respectively.
[0053] The above-mentioned glass contains Na2O as an essential component. Na2O is a component that has various functions such as increasing the specific elastic modulus of the glass, improving solubility, increasing the thermal expansion coefficient, reducing the viscosity of the glass during clarification and promoting foam bursting. In addition, among alkali metal oxides, making the glass contain Na2O can help to increase the glass transition temperature compared to the case of adding an equal amount of Li2O. The Na2O content of the above-mentioned glass is 1.00% or more, preferably 1.50% or more, and more preferably 2.00% or more, 2.50% or more, and 3.00% or more. In addition, from the perspective of increasing the glass transition temperature, the Na2O content of the above-mentioned glass is 6.00% or less, preferably 5.50% or less, and more preferably 5.00% or less, 4.50% or less, and 4.00% or less.
[0054] From the perspective of improving the water resistance of the glass, in the above-mentioned glass, the molar ratio of the SiO2 content to the Na2O content (SiO2 / Na2O) is preferably 12.0 or more, and more preferably 15.0 or more, 16.0 or more, 17.0 or more, and 18.0 or more. When the water resistance of the glass is excellent, it is preferred, for example, in terms of suppressing the roughness of the glass surface and the reduction of smoothness (i.e., the surface roughness becomes higher) when the ultra-smoothly polished glass surface comes into contact with water during cleaning. The lower the surface roughness of the glass, the easier it is for the orientation of the magnetic particles to become better. In addition, it is easy to reduce the distance between the magnetic head and the magnetic recording medium (the floating amount of the magnetic head), so it is preferred. On the other hand, from the perspective of improving the solubility of the glass, the molar ratio (SiO2 / Na2O) is preferably 50.0 or less, more preferably 40.0 or less, and further preferably 30.0 or less.
[0055] The above-mentioned glass may contain alkali metal oxides other than Na2O.
[0056] Li2O is a component having the same effect as the above-mentioned Na2O, but it is easy to lower the glass transition temperature compared with the case where an equal amount of Na2O is added as described above. The Li2O content of the above-mentioned glass can be, for example, less than 6.00%, less than 5.00%, less than 4.00%, less than 3.00%, less than 2.00%, less than 1.50%, less than 1.00%, less than 0.50%, less than 0.10%. In addition, the Li2O content of the above-mentioned glass can be 0%, more than 0% or more than 0%, more than 0.10%, more than 0.20%, more than 0.30%, more than 0.40%. In addition, the Li2O content of the above-mentioned glass can be more than 0.10% and less than 2.00%, more than 0.20% and less than 1.5%, more than 0.30% and less than 1.3%. In one embodiment, the above-mentioned glass can be a glass that does not contain Li2O.
[0057] K2O is a component having the same effect as the above-mentioned Na2O, but has a larger specific gravity than Na2O, so it is easy to reduce the specific elastic modulus compared to the case where an equal amount of Na2O is added. The K2O content of the above-mentioned glass can be, for example, less than 6.00%, less than 5.00%, less than 4.00%, less than 3.00%, less than 2.00%, less than 1.50%, less than 1.00%, less than 0.50%, or less than 0.10%. In addition, the K2O content of the above-mentioned glass can be 0%, more than 0%, or more than 0%. In one embodiment, the above-mentioned glass can be a glass that does not contain K2O. In addition, in another embodiment, the above-mentioned glass can be a glass that contains K2O, for example, it can be a glass that contains more than 0.10% K2O.
[0058] From the perspective of increasing the glass transition temperature and the specific elastic modulus, in the above-mentioned glass, the molar ratio of the Na2O content to the total content of Li2O, Na2O and K2O (Na2O / (Li2O+Na2O+K2O)) is preferably 0.350 or more, and more preferably 0.400 or more, 0.450 or more, 0.500 or more, 0.550 or more, 0.600 or more, 0.650 or more, 0.700 or more, 0.750 or more, 0.800 or more, 0.850 or more, 0.900 or more, 0.950 or more, 0.960 or more, 0.970 or more, 0.980 or more, and 0.990 or more. The molar ratio (Na2O / (Li2O+Na2O+K2O)) of the above-mentioned glass may be 1.000, or may be 1.000 or less or less than 1.000. In one embodiment, the glass may be a glass that does not contain Li2O and K2O. In addition, from the perspective of improving the water resistance and low roughness of the glass, the molar ratio (Na2O / (Li2O+Na2O+K2O)) is preferably less than 1.000, and more preferably less than 0.950 and less than 0.900, respectively.
[0059] From the perspective of improving the water resistance of the glass, in the above-mentioned glass, the molar ratio of the Li2O content to the total content of Li2O, Na2O and K2O (Li2O / (Li2O+Na2O+K2O)) is preferably 0.050 or more, and more preferably 0.100 or more. On the other hand, from the perspective of suppressing the decrease in the glass transition temperature, the molar ratio (Li2O / (Li2O+Na2O+K2O)) is preferably 0.600 or less, and more preferably 0.500 or less, 0.400 or less, and 0.300 or less, respectively.
[0060] The CaO content of the above-mentioned glass is 1.00% or less. A CaO content of 1.00% or less helps to improve the specific elastic modulus and glass transition temperature of the glass, and further helps to improve the thermal stability of the glass. From these aspects, the CaO content is preferably 0.90% or less, and more preferably 0.80% or less, 0.70% or less, 0.60% or less, 0.50% or less, 0.40% or less, 0.30% or less, 0.20% or less, and 0.10% or less. The CaO content of the above-mentioned glass can be 0%, 0% or more, or more than 0%. In one embodiment, the above-mentioned glass preferably does not contain CaO.
[0061] Regarding alkaline earth metal oxides, the CaO content of the above-mentioned glass is as described above. In one embodiment, the above-mentioned glass can contain one or more alkaline earth metal oxides. Specific examples of alkaline earth metal oxides that can be contained in the above-mentioned glass include MgO, SrO and BaO. Glass A contains MgO. From the perspective of improving rigidity, the MgO content of glass A is 14.00% or more, preferably 14.50% or more, and more preferably 15.00% or more, 15.50% or more, and 16.00% or more. In addition, from the perspective of improving the devitrification resistance of the glass, the MgO content of glass A is preferably 28.00% or less, and more preferably 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.00% or less, 22.00% or less, 21.00% or less, 20.00% or less, 19.00% or less, and 18.00% or less. Glass B can contain MgO. The description on the MgO content of Glass A can be referred to for the MgO content of Glass B.
[0062] In glass B, from the perspective of improving rigidity, the total content of MgO, SrO, CaO and BaO (MgO+SrO+CaO+BaO) is 14.00 mol% or more, preferably 14.50% or more, more preferably 15.00% or more, 15.50% or more, and 16.00% or more, in that order. In addition, from the perspective of improving the devitrification resistance of glass, the total content of MgO, SrO, CaO and BaO (MgO+SrO+CaO+BaO) of glass B is preferably 28.00% or less, more preferably 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.00% or less, 22.00% or less, 21.00% or less, 20.00% or less, 19.00% or less, and 18.00% or less, in that order. The total content of MgO, SrO, CaO and BaO in glass A (MgO+SrO+CaO+BaO) can refer to the description of the total content of MgO, SrO, CaO and BaO in glass B (MgO+SrO+CaO+BaO).
[0063] From the perspective of low specific gravity and reduced raw material costs, the SrO content of the glass is preferably 4.00% or less, preferably 3.00% or less, 2.00% or less, 1.00% or less, and 0.50% or less. In one embodiment, the SrO content of the glass can be 0%, 0% or more, or more than 0%.
[0064] From the perspective of reducing the specific gravity of the glass, increasing the Young's modulus and increasing the specific elastic modulus, the BaO content of the glass is preferably 3.00% or less, more preferably 2.00% or less, 1.00% or less, and 0.50% or less. In one embodiment, the BaO content of the glass can be 0%, 0% or more, or more than 0%.
[0065] The molar ratio of the MgO content to the total content of MgO, CaO, SrO and BaO (MgO / (MgO+CaO+SrO+BaO)) can be 1.000, less than 1.000 or less than 1.000. Compared with other alkaline earth metal oxides, MgO has a small specific gravity and can therefore help to improve the specific elastic modulus. In addition, in general glasses, the glass transition temperature tends to be increased by adding alkaline earth metal oxides with a large specific gravity. In contrast, according to the research of the present inventors, in the above-mentioned glass, if an alkaline earth metal oxide with a specific gravity greater than MgO is added, the glass transition temperature tends to be lowered. In the above-mentioned glass, from the perspective of improving the specific elastic modulus and the glass transition temperature, the molar ratio (MgO / (MgO+CaO+SrO+BaO)) is preferably greater than 0.800, and more preferably greater than 0.850, greater than 0.900, greater than 0.950, and 1.000, respectively.
[0066] From the perspective of reducing melt viscosity, lowering liquidus temperature and improving the low roughening grinding performance of glass, the molar ratio of Na2O content to MgO content (Na2O / MgO) is preferably greater than 0.080. From the perspective of molding adaptability based on various molding methods, it is preferred that the melt viscosity of the glass is low. Glass with a low liquidus temperature is preferred due to its high thermal stability. In addition, a molar ratio (Na2O / MgO) exceeding 0.080 can help reduce the resistivity of the glass melt. When the glass is electrically heated during melting, the glass with a low resistivity can reduce the temperature in the furnace during electrical heating to melt it, so it is preferred. From the above aspects, the molar ratio (Na2O / MgO) is more preferably greater than 0.090, and is further preferably greater than 0.100, greater than 0.110, greater than 0.120, greater than 0.130, greater than 0.140, greater than 0.150, and greater than 0.160. On the other hand, from the perspective of increasing the glass transition temperature and specific elastic modulus, the molar ratio (Na2O / MgO) is preferably less than 0.240, and more preferably 0.230 or less, 0.220 or less, 0.210 or less, 0.200 or less, 0.190 or less, or 0.180 or less.
[0067] Regarding TiO2, from the perspective of reducing specific gravity and improving resistance to devitrification, the TiO2 content of the above-mentioned glass is preferably 4.00% or less, and more preferably 3.00% or less, 2.00% or less, and 1.00% or less, respectively. The TiO2 content of the above-mentioned glass can be 0%, 0% or more, or more than 0%.
[0068] Regarding ZnO, from the perspective of reducing specific gravity, increasing Young's modulus and increasing specific elastic modulus, the ZnO content is preferably 10.00% or less, and more preferably 8.00% or less, 6.00% or less, 4.00% or less, 2.00% or less, and 1.00% or less. The ZnO content of the above glass can be 0%, 0% or more, or more than 0%.
[0069] The Fe2O3 content of the above-mentioned glass can be less than 1 mol%, less than 0.7 mol%, less than 0.5 mol%, less than 0.4 mol%, less than 0.3 mol%, less than 0.1 mol%, less than 0.07 mol%, less than 0.05 mol%, less than 0.04 mol%, less than 0.03 mol% or less than 0.02 mol% in terms of the content expressed by the external addition ratio (external cut). It should be noted that the Fe2O3 content is expressed by the external addition ratio. That is, when the total content of components other than Fe2O3 contained in the glass (when additives are included in addition to glass components, the total content of glass components and additives) is set to 100%, the Fe2O3 content is expressed as the molar percentage of the Fe2O3 content relative to 100%. In one embodiment, the above-mentioned glass can contain no Fe (the Fe2O3 content expressed by the above-mentioned external addition ratio is 0 mol%).
[0070] The glass may or may not contain one or more metals selected from the group consisting of Zr, Y, La, Ti, Hf, Cu, Co, Mn, Nd, Pr, Nb, V, Cr, Ni, Mo, Ho and Er, or oxides thereof. In an oxide-based glass composition, by containing one or more metal oxides selected from the group consisting of Zr, Y, La, Ti, Hf, Cu, Co, Mn, Nd, Pr, Nb, V, Cr, Ni, Mo, Ho and Er, the thermal stability of the glass tends to be improved. In one embodiment, the content of one or more metal oxides selected from the group consisting of Zr, Y, La, Ti, Hf, Cu, Co, Mn, Nd, Pr, Nb, V, Cr, Ni, Mo, Ho and Er (when two or more are included, the total content thereof) can be 0%, 0% or more, or more than 0%, and can be 5.00% or less, 4.00% or less, 3.00% or less, 2.00% or less, 1.00% or less, 0.50% or less, or 0.10% or less. For example, the Y2O3 content can be 0% or more, and can be 3.00% or less, 2.00% or less, or 1.00% or less.
[0071] F is a component that easily volatilizes during melting and is also a component that causes striae, so the glass preferably does not contain F. It is also preferable not to contain F from the perspectives of suppressing corrosion of a melting furnace, suppressing a decrease in Young's modulus, and suppressing a decrease in specific elastic modulus.
[0072] Pb, Cd, and As are substances that have adverse effects on the environment, and therefore, it is preferred to avoid introducing these components.
[0073] From the perspective of obtaining a clarification effect, the glass may contain one or more selected from the group consisting of SnO2, CeO2 and Sb2O3. In one embodiment, the total content of SnO2 and CeO2 can be 0%. In another embodiment, the glass may contain SnO2 and / or CeO2, and the total content of SnO2 and CeO2 (SnO2+CeO2) is preferably 0.05-2%. By making the total content of SnO2 and CeO2 more than 0.05%, a sufficient clarification effect can be obtained and the residual bubbles can be reduced. In addition, by making the total content (SnO2+CeO2) less than 2%, it is possible to prevent the molten glass from floating up during glass melting and reducing productivity. The lower limit of the total content (SnO2+CeO2) is preferably 0.10% or more, more preferably 0.20% or more, further preferably 0.25% or more, more preferably 0.30% or more, further preferably 0.35% or more, and further more preferably 0.40% or more. In addition, the upper limit of the total content (SnO2+CeO2) is preferably 1.5% or less, more preferably 1.2% or less, further preferably 1.0% or less, further preferably 0.70% or less, further preferably 0.65% or less, further preferably 0.60% or less, further preferably 0.55% or less, and further preferably 0.50% or less.
[0074] SnO2 has the effect of promoting clarification when the melting temperature of the glass is relatively high (temperature range of about 1400-1600°C). In the case where the use of clarifiers such as Sb2O3 and arsenic acid that have adverse effects on the environment is restricted, in order to remove glass bubbles with a high melting temperature, in one embodiment, SnO2 is preferably introduced into the above-mentioned glass. From the perspective of obtaining a clarification effect, the content of SnO2 is preferably 0.01% or more, more preferably 0.05% or more, further preferably 0.10% or more, more preferably 0.15% or more, and further preferably 0.20% or more. In addition, the content of SnO2 is preferably 2% or less, more preferably 1.5% or less, further preferably 1.0% or less, further preferably 0.8% or less, and further preferably 0.5% or less.
[0075] CeO2 is a component that exhibits a clarifying effect on glass, similarly to SnO2. CeO2 has the effect of absorbing oxygen and fixing it as a glass component when the melting temperature of the glass is relatively low (temperature range of about 1200 to 1400°C), so in one embodiment, CeO2 is preferably introduced into the above-mentioned glass as a clarifying agent. From the perspective of obtaining a clarifying effect, the content of CeO2 is preferably 0.01% or more, more preferably 0.05% or more, further preferably 0.08% or more, and more preferably 0.10% or more. In addition, the content of CeO2 is preferably 2% or less, more preferably 1.5% or less, further preferably 1.0% or less, further preferably 0.8% or less, further preferably 0.5% or less, and further preferably 0.3% or less. By allowing SnO2 and CeO2 to coexist, a clarifying effect can be obtained in a wide temperature range, so in one embodiment, the above-mentioned glass preferably contains both SnO2 and CeO2.
[0076] From the perspective of reducing environmental burden, it is preferred to control the use of Sb2O3. The content of Sb2O3 in the above-mentioned glass is preferably in the range of 0 to 0.5%. The content of Sb2O3 is more preferably 0.3% or less, further preferably 0.1% or less, further preferably 0.05% or less, further preferably 0.02% or less, and particularly preferably no Sb2O3 is contained.
[0077] In order to obtain a predetermined glass composition, the glass can be produced as follows: glass raw materials such as oxides, carbonates, nitrates, sulfates, hydroxides, etc. are weighed and mixed, and then heated, melted, clarified, stirred, and fully defoamed and homogenized in a melting container, and the obtained molten glass is molded to produce the glass. For example, it is preferred that the glass raw materials are heated and melted in a melting tank at 1400 to 1550° C., the obtained molten glass is heated and maintained at 1450 to 1600° C. in a clarification tank, and then the temperature is lowered and the glass is made to flow out at 1200 to 1400° C. to be molded.
[0078] According to one embodiment of the present invention, there is provided a glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, which is the following amorphous glass:
[0079] The B2O3 content is 0.1 mol% or more and 2.0 mol% or less,
[0080] The Na2O content is 1.0 mol% or more and 6.0 mol% or less, and
[0081] The CaO content is 0 mol% or more and 1.0 mol% or less,
[0082] Furthermore, at least one of the following (1) to (10) is satisfied.
[0083] (1) The molar ratio (Na2O / (Li2O+Na2O+K2O)) is 0.950 or more, and the total content (SiO2+B2O3+Al2O3) is 70.00% or more.
[0084] (2) Li2O and K2O are not contained, and the total content (SiO2+B2O3+Al2O3) is 70.00% or more.
[0085] (3) The molar ratio (Na2O / (Li2O+Na2O+K2O)) is 0.950 or more, and the total content (SiO2+B2O3) is 58.00% or more.
[0086] (4) Li2O and K2O are not contained, and the total content (SiO2+B2O3) is 58.00% or more.
[0087] (5) The molar ratio (Na2O / (Li2O+Na2O+K2O)) is 0.950 or more, and the total content (SiO2+Al2O3) is 70.00% or more.
[0088] (6) Li2O and K2O are not contained, and the total content (SiO2+Al2O3) is 70.00% or more.
[0089] (7) The molar ratio (Na2O / (Li2O+Na2O+K2O)) is greater than 0.950, and the TiO2 content is less than 4.00 mol%.
[0090] (8) Li2O and K2O are not contained, and the TiO2 content is 4.00 mol% or less.
[0091] (9) The molar ratio (Na2O / (Li2O+Na2O+K2O)) is 0.950 or more, and the ZnO content is 10.00% or less.
[0092] (10) Li2O and K2O are not contained, and the ZnO content is 10.00% or less.
[0093] Regarding the above-mentioned glasses, the above-mentioned description on the compositions of glass A and glass B and the following description on the physical properties of glass A and glass B can be referred to.
[0094] According to one embodiment of the present invention, there is provided a glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device (hereinafter referred to as "glass a"), which is the following amorphous glass,
[0095] The B2O3 content is 0.10 mol% or more and 2.00 mol% or less,
[0096] The total content of Na2O and K2O is 1.00 mol% or more and 6.00 mol% or less,
[0097] The CaO content is 0 mol% or more and 1.00 mol% or less,
[0098] MgO content is 14.00 mol% or more;
[0099] A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device (hereinafter referred to as "glass b"), which is the following amorphous glass,
[0100] The B2O3 content is 0.10 mol% or more and 2.00 mol% or less,
[0101] The total content of Na2O and K2O is 1.00 mol% or more and 6.00 mol% or less,
[0102] The CaO content is 0 mol% or more and 1.00 mol% or less,
[0103] The total content of MgO, SrO, CaO and BaO (MgO+SrO+CaO+BaO) is 14.00 mol% or more.
[0104] Regarding glass a and glass b, reference can be made to the above description regarding the compositions of glass A and glass B and the following description regarding the physical properties of glass A and glass B.
[0105] <Glass Properties>
[0106] By adjusting the composition as described above, the glass can have the various glass properties described below.
[0107] (Specific elastic modulus)
[0108] By having the composition described above, the glass can have high rigidity. As an index of the rigidity of the glass, the specific elastic modulus can be cited. The specific elastic modulus is calculated by dividing the Young's modulus of the glass by the density. The density here can be regarded as the specific gravity of the glass in g / cm 3The value obtained by this unit. The specific elastic modulus of the above-mentioned glass is preferably 35.0MNm / kg or more, and is further preferably 35.5MNm / kg or more, 36.0MNm / kg or more, 36.5MNm / kg or more, and 37.0MNm / kg or more. The specific elastic modulus can be, for example, 45.0MNm / kg or less, 44.0MNm / kg or less, 43.0MNm / kg or less, 42.0MNm / kg or less, 41.0MNm / kg or less, 40.0MNm / kg or less, 39.0MNm / kg or less, or 38.0MNm / kg or less. The higher the specific elastic modulus, the higher the rigidity, which is preferred, and is not limited to the values exemplified above. It should be noted that, regarding the above-mentioned glass, considering the balance with the glass transition temperature, the specific elastic modulus can be 37.0MNm / kg or less.
[0109] (Young's modulus E)
[0110] As an index of the rigidity of glass, Young's modulus can also be cited. The Young's modulus of the above-mentioned glass is preferably 86.0GPa or more, more preferably 87.0GPa or more, and more preferably 88.0GPa or more, 89.0GPa or more, 90.0GPa or more, 91.0GPa or more, 92.0GPa or more, and 93.0GPa or more. The Young's modulus of the above-mentioned glass can be, for example, below 120.0GPa, below 110.0GPa, below 100GPa or below 95.0GPa. The higher the Young's modulus, the higher the rigidity, which is preferred, and is therefore not limited to the values exemplified above. It should be noted that, regarding the above-mentioned glass, considering the balance with the glass transition temperature, the Young's modulus can be made below 94.0GPa, below 93.0GPa or below 92.0GPa.
[0111] (Specific gravity d)
[0112] By reducing the specific gravity of the glass for the magnetic recording medium substrate, the magnetic recording medium substrate can be lightweight, and the magnetic recording medium can be lightweight, thereby suppressing the power consumption of the HDD. The specific gravity of the above-mentioned glass is preferably below 2.80, more preferably below 2.75, further preferably below 2.70, further preferably below 2.65, and further preferably below 2.60. The specific gravity of the above-mentioned glass can be, for example, above 2.40, and the lower the specific gravity, the more preferred it is, and thus it is not limited to the values exemplified above.
[0113] (Glass transition temperature Tg)
[0114] The magnetic recording medium substrate is usually subjected to high temperature treatment in the process of forming the magnetic recording layer on the substrate. For example, in order to form a magnetic recording layer containing a magnetic material with high magnetic anisotropy energy developed in recent years to realize high-density recording of magnetic recording media, film formation is usually carried out at high temperature, or heat treatment is carried out at high temperature after film formation. If the magnetic recording medium substrate has heat resistance that can withstand such high temperature treatment, it is preferred to prevent the flatness of the substrate from being reduced when exposed to high temperature. In this regard, by having the above-mentioned glass composition, the above-mentioned glass can also show high heat resistance. Regarding the glass transition temperature Tg as an index of heat resistance, the Tg of the glass can be, for example, 550°C or higher, preferably 600°C or higher, and more preferably 610°C or higher, 620°C or higher, 630°C or higher, 640°C or higher, 650°C or higher, 660°C or higher, 670°C or higher, 680°C or higher, 690°C or higher, 700°C or higher, 710°C or higher, 720°C or higher, 730°C or higher, 740°C or higher, and 750°C or higher. In addition, the Tg of the glass can be, for example, 850°C or lower, 830°C or lower, 810°C or lower, 790°C or lower, 770°C or lower, or 750°C or lower. The higher the Tg, the more preferred it is from the viewpoint of heat resistance, and therefore, it is not limited to the values exemplified above.
[0115] (Thermal stability)
[0116] The glass preferably exhibits high thermal stability. As a method for evaluating thermal stability, a 1300°C 16-hour holding test and a 1320°C 16-hour holding test described in detail below can be cited. In the 1300°C 16-hour holding test, the evaluation result is preferably A or B, more preferably A. In the 1320°C 16-hour holding test, the evaluation result is preferably A or B, more preferably A.
[0117] (Liquid phase temperature LT)
[0118] As an index of thermal stability of glass, liquidus temperature (LT) can be cited. LT of the above-mentioned glass is preferably 1330°C or less, more preferably 1320°C or less, and further preferably 1310°C or less, 1300°C or less, 1290°C or less, 1280°C or less, 1270°C or less, 1260°C or less, 1250°C or less, and 1240°C or less. Glass with a low liquidus temperature LT is less likely to lose clarity and is therefore preferred. The lower limit of LT can be, for example, 800°C or more, but is not particularly limited.
[0119] (Coefficient of thermal expansion)
[0120] An HDD in which a magnetic recording medium is assembled usually has a structure in which the central portion is clamped by the spindle of a spindle motor and a chuck to rotate the magnetic recording medium itself. Therefore, if the thermal expansion coefficients of the magnetic recording medium substrate and the spindle material constituting the spindle portion are greatly different, then during use, the thermal expansion and contraction of the spindle will deviate from the thermal expansion and contraction of the magnetic recording medium substrate relative to the ambient temperature changes, resulting in deformation of the magnetic recording medium. If such a phenomenon occurs, the magnetic head will not be able to read the written information, which will cause a decrease in the reliability of recording and reproducing. Therefore, it is preferred that the difference between the thermal expansion coefficient of the glass used for the magnetic recording medium substrate and the thermal expansion coefficient of the spindle material (such as stainless steel, etc.) should not be too large. Usually, the spindle material of the HDD has a thermal expansion coefficient of 70×10 -7 / ℃ or above, if the average linear expansion coefficient of the glass used for the magnetic recording medium substrate is 30.0×10 -7 / ℃ or more, the difference in thermal expansion coefficient with the main shaft material is small, which can help improve the reliability of the magnetic recording medium. On the other hand, if the thermal expansion coefficient of the glass substrate is too large, the substrate may sometimes break due to heating during film formation. The average linear expansion coefficient α of glass 2 at 100 to 300℃ is preferably 34.0×10 -7 / ℃ or more, and more preferably 35.0×10 -7 / ℃ or above, 36.0×10 -7 / ℃ or above, 37.0×10 -7 / ℃ or above, 38.0×10 -7 / ℃ or above, 39.0×10 -7 / ℃ or above, 40.0×10 -7 / °C or more. In addition, the average linear expansion coefficient α of the glass 2 at 100 to 300°C is preferably 70.0×10 -7 / ℃ or less, and more preferably 68.0×10 -7 / ℃ below, 65.0×10 -7 / ℃ below, 63.0×10 -7 / ℃ below, 60.0×10 -7 / ℃ or less, 57.0×10 -7 / ℃ or less, 55.0×10 -7 / ℃ or less, 50.0×10 -7 / ℃ below.
[0121] The above-mentioned various physical properties can be obtained by the methods described later in Examples.
[0122] [Magnetic recording medium substrate]
[0123] A magnetic recording medium substrate according to one embodiment of the present invention is composed of the above-mentioned glass.
[0124] The magnetic recording medium substrate can be manufactured through the following process: preparing molten glass by heating glass raw materials, forming the molten glass into a plate-like shape by any method such as a press forming method, a down-drawing method or a float method, and processing the obtained plate-like glass. For example, in the press forming method, the molten glass flowing out of the glass outflow tube is cut into a specified volume to obtain a desired molten glass block, which is press-formed using a press forming mold to produce a thin-walled disc-shaped substrate blank. Next, a center hole is set in the obtained substrate blank, inner and outer circumference processing is applied, and grinding processing such as polishing and polishing is applied to the two main surfaces. Next, a disc-shaped substrate can be obtained through a cleaning process including acid cleaning and alkali cleaning. Regarding the various processes performed to obtain the above-mentioned magnetic recording medium substrate, the known technology for the manufacture of the magnetic recording medium substrate can be applied.
[0125] In one embodiment, the surface and internal composition of the magnetic recording medium substrate are homogeneous. Here, the surface and internal composition are homogeneous means that ion exchange is not performed (i.e., there is no ion exchange layer). The magnetic recording medium substrate without an ion exchange layer is manufactured without ion exchange treatment, so the manufacturing cost can be greatly reduced.
[0126] In addition, in one embodiment, a part or all of the surface of the magnetic recording medium substrate has an ion exchange layer. Since the ion exchange layer shows compressive stress, the presence or absence of the ion exchange layer can be confirmed by cutting the substrate perpendicularly relative to the main surface and obtaining stress distribution in the fracture surface according to the Babinet method. The "main surface" is the surface of the substrate where the magnetic recording layer is set or the surface where the magnetic recording layer is set. Such a surface is the surface with the largest area in the surface of the magnetic recording medium substrate, so it is called the main surface. In the case of a disc-shaped magnetic recording medium, it is equivalent to the circular surface of the disc (without the center hole). In addition, the presence or absence of the ion exchange layer can also be confirmed by a method for measuring the concentration distribution of alkali metal ions from the substrate surface along the depth direction.
[0127] The ion exchange layer can be formed by contacting the substrate surface with an alkali metal salt at a high temperature and exchanging the alkali metal ions in the alkali metal salt with the alkali metal ions in the substrate. Regarding ion exchange (also called "strengthening treatment" or "chemical strengthening"), known techniques can be applied. As an example, reference can be made to paragraphs 0068 to 0069 of WO2011 / 019010A1.
[0128] The thickness of the magnetic recording medium substrate is, for example, less than 1.5 mm, preferably less than 1.2 mm, more preferably less than 1.0 mm, further preferably less than 0.8 mm, more preferably less than 0.8 mm, further preferably less than 0.7 mm, and further more preferably less than 0.6 mm. In addition, the thickness of the magnetic recording medium substrate is, for example, more than 0.2 mm. From the aspect of improving the recording capacity of the HDD, it is preferred that the thickness of the magnetic recording medium substrate can be reduced. In addition, the magnetic recording medium substrate is preferably a disk-shaped substrate with a center hole.
[0129] The magnetic recording medium substrate is made of amorphous glass. Amorphous glass can achieve excellent surface smoothness when processed into a substrate compared to crystallized glass.
[0130] Since the magnetic recording medium substrate is composed of the glass of one embodiment of the present invention, it can have the glass properties described above for the glass.
[0131] [Magnetic recording media]
[0132] One embodiment of the present invention relates to a magnetic recording medium including the magnetic recording medium substrate and a magnetic recording layer.
[0133] Magnetic recording media are called magnetic disks, hard disks, etc., and are suitable for various magnetic recording and reproducing devices, such as internal storage devices (local hard disks, etc.) of desktop computers, server computers, notebook computers, mobile personal computers, etc., internal storage devices of portable recording and reproducing devices that record and reproduce images and / or sounds, and recording and reproducing devices for car audio. In the present invention and this specification, a "magnetic recording and reproducing device" refers to a device that can perform one or both of magnetic recording and magnetic reproducing of information.
[0134] The magnetic recording medium has a structure in which at least an adhesion layer, an underlayer, a magnetic layer (magnetic recording layer), a protective layer, and a lubricating layer are stacked in order from the side close to the main surface on the main surface of a magnetic recording medium substrate.
[0135] For example, a magnetic recording medium substrate is introduced into a film forming device after vacuuming, and a DC (direct current) magnetron sputtering method is used to form films in sequence from an adhesion layer to a magnetic layer on the main surface of the magnetic recording medium substrate in an Ar atmosphere. As an adhesion layer, for example, CrTi can be used, and as a base layer, for example, a material containing Ru or MgO can be used. It should be noted that a soft magnetic layer and a heat dissipation layer can also be appropriately added. After the above-mentioned film formation, for example, a protective layer is formed using C2H4 by a CVD (chemical vapor deposition) method, and a nitriding treatment of introducing nitrogen into the surface is performed in the same chamber, thereby forming a magnetic recording medium. Thereafter, for example, PFPE (perfluoropolyether) is applied to the protective layer by a dip coating method, thereby forming a lubricating layer.
[0136] In order to further increase the density of recording in the magnetic recording medium, the magnetic recording layer preferably contains a magnetic material with high magnetic anisotropy energy. As a preferred magnetic material from this aspect, Fe-Pt-based magnetic materials or Co-Pt-based magnetic materials can be cited. It should be noted that "based" here means containing. That is, the above-mentioned magnetic recording medium can have a magnetic recording layer containing Fe and Pt, or Co and Pt as a magnetic recording layer. Regarding the magnetic recording layer containing the magnetic material and the film forming method thereof, reference can be made to paragraph 0074 of WO2011 / 019010A1 and the description of the embodiments of the gazette. In addition, the magnetic recording medium having such a magnetic recording layer is preferably suitable for a magnetic recording device using a recording method called an energy-assisted recording method. Among the energy-assisted recording methods, the recording method that assists the magnetization reversal by irradiation with near-field light or the like is called a thermally assisted recording method, and the recording method that assists by microwaves is called a microwave-assisted recording method. For their details, reference can be made to paragraph 0075 of WO2011 / 019010A1. It should be noted that as the magnetic material for forming the magnetic recording layer, a conventional CoPtCr-based material can be used.
[0137] In addition, in recent years, the gap between the recording and reproducing element part of the magnetic head and the surface of the magnetic recording medium has been greatly narrowed (low suspension quantization) by equipping the magnetic head with a DFH (Dynamic Flying Height) mechanism, thereby achieving further high recording density. The DFH mechanism refers to a function in which a very small heating part such as a heater is provided near the recording and reproducing element part of the magnetic head, and only the periphery of the element part protrudes toward the surface of the medium. In this way, the distance (flying height) between the magnetic head and the magnetic recording layer of the medium is close, so that the signal of smaller magnetic particles can be picked up, and further high recording density can be achieved. In one embodiment, the above-mentioned magnetic recording medium substrate can be used as a substrate of a magnetic recording medium suitable for a magnetic recording and reproducing device having a magnetic head equipped with a DFH mechanism.
[0138] The size of the magnetic recording medium substrate (e.g., glass substrate for magnetic disk) and the magnetic recording medium (e.g., magnetic disk) is not particularly limited. For example, since high recording density can be achieved, the medium and the substrate can be miniaturized. In addition, in order to increase the recording capacity of each magnetic recording medium, the medium and the substrate can also be enlarged. For example, the nominal diameter can certainly be 2.5 inches, and further can be set to a small diameter (e.g., 1 inch, 1.8 inches), or 3 inches, 3.5 inches, and a size larger than it.
[0139] [Glass spacer for magnetic recording and reproducing device]
[0140] A glass spacer for a magnetic recording and reproducing device (hereinafter also simply referred to as a “glass spacer”) according to one embodiment of the present invention is made of the above-mentioned glass.
[0141] Magnetic recording media can be used for magnetic recording and / or reproducing information in a magnetic recording and reproducing device. In a magnetic recording and reproducing device, a spacer is usually provided in order to fix the magnetic recording medium to the main shaft of a spindle motor and / or to maintain a distance between two or more magnetic recording media. In recent years, a scheme of using a glass spacer has been proposed as the spacer. For reasons similar to those described in detail above regarding the glass for the magnetic recording medium substrate, it is preferred that the glass spacer also has high rigidity. In this regard, the glass having the above composition is suitable as a glass spacer for a magnetic recording and reproducing device because it can have high rigidity.
[0142] The spacer used in the magnetic recording and reproducing device is an annular component, and the details of the composition and manufacturing method of the glass spacer are well known. In addition, regarding the manufacturing method of the glass spacer, reference can also be made to the above-mentioned description on the manufacturing method of the glass for the magnetic recording medium substrate and the manufacturing method of the magnetic recording medium substrate. In addition, regarding other details such as the glass composition and glass properties of the above-mentioned glass spacer, reference can be made to the above-mentioned description on the above-mentioned glass, the magnetic recording medium substrate composed of the above-mentioned glass, and the magnetic recording medium having the magnetic recording medium substrate.
[0143] It should be noted that the spacer for the magnetic recording and reproducing device can be composed of the above-mentioned glass spacer, or can also be composed of a film such as a conductive film provided on the surface of the above-mentioned glass spacer. For example, in order to remove the static electricity generated when the magnetic recording medium rotates, a conductive film such as a NiP alloy can be formed on the surface of the glass spacer by plating, dipping, evaporation, sputtering, etc. In addition, the glass spacer can be polished to improve the surface smoothness (for example, the average surface roughness Ra is less than 1 μm), thereby enhancing the closeness between the magnetic recording medium and the spacer, and suppressing the occurrence of position deviation.
[0144] [Magnetic recording and reproducing device]
[0145] One embodiment of the present invention relates to a magnetic recording and reproducing device including one or more selected from the group consisting of the above-mentioned magnetic recording medium and the above-mentioned glass spacer.
[0146] A magnetic recording and reproducing device includes at least one magnetic recording medium and at least one spacer, and further generally includes a spindle motor for rotationally driving the magnetic recording medium and at least one magnetic head for recording and / or reproducing information on the magnetic recording medium.
[0147] The magnetic recording and reproducing device of one embodiment of the present invention may include a magnetic recording medium of one embodiment of the present invention as at least one magnetic recording medium, or may include two or more magnetic recording media of one embodiment of the present invention. The magnetic recording and reproducing device of one embodiment of the present invention may include a glass spacer of one embodiment of the present invention as at least one spacer, or may include two or more glass spacers of one embodiment of the present invention. From the perspective of suppressing the occurrence of phenomena that may be caused by the difference in thermal expansion coefficients of the two (for example, the reduction in stability during rotation caused by the strain of the magnetic recording medium and the positional deviation of the magnetic recording medium), it is preferred that the difference between the thermal expansion coefficient of the magnetic recording medium and the thermal expansion coefficient of the spacer is small. From this perspective, in the magnetic recording and reproducing device of one embodiment of the present invention, it is preferred that the magnetic recording medium of one embodiment of the present invention is included as at least one magnetic recording medium, and as more magnetic recording media when it includes two or more magnetic recording media; and it is preferred that the glass spacer of one embodiment of the present invention is included as at least one spacer, and as more spacers when it includes two or more spacers. Furthermore, for example, in the magnetic recording and reproducing device of one embodiment of the present invention, the glass constituting the magnetic recording medium substrate included in the magnetic recording medium and the glass constituting the glass spacer can have the same glass composition.
[0148] The magnetic recording and reproducing device of one embodiment of the present invention only needs to include at least one of the magnetic recording medium of one embodiment of the present invention and the glass spacer of one embodiment of the present invention, and the known technology of the magnetic recording and reproducing device can be applied to other aspects. In one embodiment, as a magnetic head, an energy-assisted magnetic recording head having an energy source (such as a heat source such as a laser source, microwave, etc.) for assisting magnetization reversal (assisting the writing of magnetic signals), a recording element part and a reproducing element part can be used. The magnetic recording and reproducing device of the energy-assisted recording method including such an energy-assisted magnetic recording head is useful as a magnetic recording and reproducing device with high recording density and high reliability. In addition, when manufacturing a magnetic recording medium used in a magnetic recording and reproducing device of an energy-assisted recording method such as a thermally assisted recording method (equipped with a thermally assisted magnetic recording head having a laser source, etc.), sometimes a magnetic recording layer containing a magnetic material with high magnetic anisotropy energy is formed on a magnetic recording medium substrate. In order to form such a magnetic recording layer, film formation is usually performed at a high temperature, or heat treatment is performed at a high temperature after film formation. Regarding the magnetic recording medium substrate of one embodiment of the present invention, in one embodiment, it can be a magnetic recording medium substrate with high heat resistance that can withstand such high temperature treatment. However, the magnetic recording and reproducing device according to one embodiment of the present invention is not limited to an energy-assisted magnetic recording and reproducing device.
[0149] Example
[0150] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the embodiments shown in the examples.
[0151] [Examples 1 to 19]
[0152] In order to obtain the glass of the composition shown in Table 1, raw materials such as oxides, carbonates, nitrates, sulfates, hydroxides, etc. were weighed and mixed to prepare a blended raw material. The blended raw material was put into a melting tank, heated and melted in the range of 1400 to 1600° C., and the obtained molten glass was kept at 1400 to 1550° C. in a clarification tank for 6 hours, and then the temperature was lowered (cooled down), and after being kept in the range of 1200 to 1400° C. for 1 hour, the molten glass was molded to obtain glass (amorphous oxide glass) for the following evaluation.
[0153] <Evaluation of Glass Properties>
[0154] (1) Glass transition temperature Tg, average linear expansion coefficient α
[0155] The glass transition temperature Tg and the average linear expansion coefficient α at 100 to 300° C. of each glass were measured using a thermomechanical analyzer (TMA).
[0156] (2) Young's modulus E
[0157] The Young's modulus of each glass was measured by an ultrasonic method.
[0158] (3) Specific gravity d
[0159] The specific gravity of each glass was measured by the Archimedean method.
[0160] (4) Specific elastic modulus
[0161] The specific elastic modulus was calculated from the Young's modulus obtained in (2) and the specific gravity obtained in (3).
[0162] (5) 1300℃ 16h holding test
[0163] 100g of each glass was placed in a platinum crucible, and each crucible was placed in a heating furnace with the furnace temperature set at 1300°C, and placed for 16 hours (holding test) while maintaining the furnace temperature. After 16 hours, the crucible was taken out from the heating furnace, and the glass in the crucible was transferred to a refractory, cooled to room temperature (20°C to 25°C), and the presence or absence of crystallization of each glass was observed with an optical microscope (magnification 40 to 100 times), and evaluated according to the following criteria.
[0164] A: There is no crystallization on the glass surface, inside, or at the interface with the bottom of the platinum crucible.
[0165] B: On the glass surface and at the interface with the bottom of the platinum crucible, the number of crystals with a diameter of tens of μm is less than 10 / 100g.
[0166] C: At the interface between the glass surface and the bottom of the platinum crucible, there are more than 10 crystals with a diameter of tens of μm / 100g
[0167] D: There are crystals inside the glass
[0168] E: Crystals are present on the glass surface, inside, and at the interface with the bottom of the platinum crucible.
[0169] F: There are a lot of crystals in the glass as a whole, and it is a bit blurry
[0170] G: Glass is cloudy
[0171] (6) 1320℃ 16h holding test
[0172] The holding test and the evaluation of the glass after the holding test were performed by the method described in the above (5) except that the temperature in the furnace was set to 1320°C.
[0173] (7) Liquidus temperature LT
[0174] The liquidus temperatures of the glasses shown in the tables below were determined by the following method.
[0175] Weigh 50g of glass in a platinum crucible. Cover the platinum crucible with a platinum lid and place it in a heating furnace with an atmosphere temperature of 1350°C. After the glass in the crucible is completely molten, the atmosphere temperature in the furnace is lowered to a specified temperature and maintained at this temperature for 16 hours. After 16 hours, take the platinum crucible out of the furnace and place it to cool the glass to room temperature (about 20°C to 25°C). Visually observe the cooled glass to check whether there is any crystal precipitation.
[0176] The above operation was performed at intervals of 10°C from 1330°C to 1200°C, and the lowest temperature at which no crystal precipitation was observed was defined as the liquidus temperature LT.
[0177] (8) Roughness evaluation
[0178] The method described later is used to make a glass substrate for a magnetic disk having each glass composition shown in the table described later. Here, the basic processing conditions such as grinding conditions and cleaning conditions are the same. The arithmetic mean roughness Ra (JIS B0601: 2001) of the main surface of the magnetic disk glass substrate after the final cleaning is measured by AFM (atomic force microscope).
[0179] Ra measured for each glass is expressed as a relative value (ratio) when the value of Ra measured for Example 4 is set to 1.00. The degree of roughness is graded according to the following criteria. It should be noted that grade C also has no practical problems.
[0180] Grade A: less than 0.80
[0181] Grade B: 0.80 or more and less than 0.90 Grade C: 0.90 or more and 1.00 or less The above results are shown in the following table.
[0182] [Table 1]
[0183]
[0184] [Table 2]
[0185]
[0186] [Table 3]
[0187]
[0188] [Table 4]
[0189]
[0190] [Table 5]
[0191]
[0192] <Fabrication of Magnetic Recording Medium Substrate>
[0193] (1) Preparation of substrate blanks
[0194] A disk-shaped substrate blank is produced by the following method A or B. In addition, a glass blank for producing a glass spacer for a magnetic recording and reproducing device can be obtained by the same method.
[0195] (Method A)
[0196] For the glass of the composition shown in Table 1, the clarified, homogenized molten glass is flowed out from the outflow pipe at a constant flow rate and is received by the lower mold for press molding at the same time, and the molten glass flowing out is cut off with a cutting blade so that a specified amount of molten glass blocks are obtained on the lower mold. Immediately thereafter, the lower mold carrying the molten glass block is moved out from the bottom of the tube, and the upper mold and the cylindrical mold opposed to the lower mold are press molded into a thin-walled disc with a diameter of 99mm and a thickness of 0.7mm. After the press molded product is cooled to a temperature where no deformation occurs, it is taken out from the mold and annealed to obtain a substrate blank (amorphous oxide glass). It should be noted that in the above-mentioned molding, more than two lower molds are used to successively mold the molten glass flowing out into a disc-shaped substrate blank.
[0197] (Method B)
[0198] For the glass having the composition shown in Table 1, the clarified and homogenized molten glass was continuously cast from the top into the through hole of a heat-resistant casting mold provided with a cylindrical through hole, formed into a cylindrical shape and taken out from the lower side of the through hole. After annealing the taken out glass, the glass was sliced at regular intervals in a direction perpendicular to the cylindrical axis using a multi-wire cutter to produce a disc-shaped substrate blank (amorphous oxide glass).
[0199] It should be noted that, in this embodiment, the above-mentioned methods A and B are used, but as a method for manufacturing a disk-shaped substrate blank, the following methods C and D are also suitable. In addition, the following methods C and D are also suitable as a method for manufacturing a glass blank for making a glass spacer for a magnetic recording and reproducing device.
[0200] (Method C)
[0201] Alternatively, the molten glass may be flowed onto a float bath and formed into a sheet of glass (forming by a float process), and then, after annealing, a disc of glass may be cut out from the sheet of glass to obtain a substrate blank (amorphous oxide glass).
[0202] (Method D)
[0203] Alternatively, the molten glass may be formed into a sheet of glass by an overflow down-draw method (fusion method), annealed, and then a disk of glass may be dug out from the sheet of glass to obtain a substrate blank (amorphous oxide glass).
[0204] (2) Preparation of glass substrate
[0205] A through hole is opened in the center of the substrate blank (amorphous oxide glass) obtained by the above methods, and the outer and inner circumferences are ground (chamfered surfaces are formed at the same time), and the end surface is ground, and the main surface of the disk is polished and polished (mirror polishing) to be finished into a magnetic disk glass substrate with an outer diameter of 97mm, an inner diameter of 25mm, and a thickness of 0.5mm. In addition, the glass blank used for making a glass spacer for a magnetic recording and reproducing device can be finished into a glass spacer for a magnetic recording and reproducing device by the same method.
[0206] After the above-obtained glass substrate is scrubbed and cleaned, it is cleaned with potassium hydroxide aqueous solution, and then dried after being rinsed with pure water. The surface of the substrate made of the glass of the embodiment is observed by atomic force microscope (AFM), and the surface roughness is not confirmed, and it is a smooth (low roughness) surface.
[0207] <Manufacturing of Magnetic Recording Media (Magnetic Disks)>
[0208] An adhesion layer, a base layer, a magnetic recording layer, a protective layer, and a lubricating layer were sequentially formed on the main surface of the magnetic disk glass substrate produced as described above by the following method to obtain a magnetic disk.
[0209] First, using a vacuum film forming apparatus, an adhesion layer, a base layer, and a magnetic recording layer were sequentially formed in an Ar atmosphere by a DC magnetron sputtering method.
[0210] At this time, a CrTi target was used to form a film so that the adhesion layer became an amorphous CrTi layer with a thickness of 20 nm. Next, a 10 nm thick layer composed of MgO was formed as a base layer. In addition, a FePtC or CoPtC target was used to form a film at a film forming temperature of 200 to 400° C. so that the magnetic recording layer became a granular layer of FePt or CoPt with a thickness of 10 nm.
[0211] After the magnetic recording layer is formed, the magnetic disk is transferred from the film forming device to a heating furnace for annealing. The temperature in the heating furnace during annealing is set in the range of 500 to 700°C. Through this annealing process, L 10 It should be noted that the above contents are not limited to the above contents, as long as the L 10 For example, the L can be formed by heating the magnetic recording layer in a regular structure by setting the substrate temperature to 500 to 700° C. when forming a FePt or CoPt magnetic recording layer. 10 Rule structure.
[0212] Next, a protective layer of 3 nm made of hydrogenated carbon was formed by CVD using ethylene as a material gas, and then a lubricating layer made of PFPE (perfluoropolyether) was formed by dip coating. The film thickness of the lubricating layer was 1 nm.
[0213] Obtain magnetic disk by the above manufacturing process. Obtained magnetic disk is carried on the hard disk drive having DFH mechanism, and the recording on the main surface of magnetic disk is used in the area with the recording density of 1000Gbit per 1 square inch to carry out recording and regeneration of magnetic signal, and the result does not confirm the phenomenon (scratching fault) that magnetic head collides with magnetic disk surface.
[0214] In addition, a glass spacer was obtained by the above-mentioned manufacturing process using the glass of the composition shown in Table 1, and a spacer having a conductive film of NiP alloy formed on the surface of the glass spacer (glass spacer with NiP alloy film) was mounted on a hard disk drive having a DFH mechanism. A magnetic disk was separately prepared using a substrate made of a material different from the glass of one embodiment of the present invention, and magnetic signals were recorded and reproduced in a recording area on the main surface of the magnetic disk at a recording density of 1000 Gbit per square inch. As a result, no collision between the magnetic head and the magnetic disk surface (scratch failure) was confirmed.
[0215] In addition, the above-manufactured magnetic disk and the above-manufactured glass spacer with NiP alloy film were mounted on a hard disk drive having a DFH mechanism using the same glass material as one embodiment of the present invention, and magnetic signals were recorded and reproduced at a recording density of 1000 Gbit per square inch in the recording area on the main surface of the magnetic disk. As a result, no collision between the magnetic head and the magnetic disk surface (scratching failure) was confirmed. Here, since the glass substrate included in the above-mentioned magnetic disk and the above-mentioned glass spacer are made of the same glass material, the phenomenon that may occur due to the difference in the above-mentioned thermal expansion coefficient does not occur.
[0216] According to one embodiment of the present invention, it is possible to provide a magnetic recording medium suitable for high-density recording.
[0217] It should be understood that the embodiments disclosed this time are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0218] For example, the glass composition exemplified above can be used to produce the glass for a magnetic recording medium substrate and the glass spacer for a magnetic recording and reproducing device according to one embodiment of the present invention by adjusting the composition as described in the specification.
[0219] Furthermore, it is of course possible to arbitrarily combine two or more of the items exemplified or described as the preferred range in the specification.
Claims
1. A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, which is the following amorphous glass, The B2O3 content is 0.10 mol% or more and 2.00 mol% or less, The Na2O content is 1.00 mol% or more and 6.00 mol% or less, The CaO content is 0 mol% or more and 1.00 mol% or less, The MgO content is 14.00 mol % or more.
2. A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, which is the following amorphous glass, The B2O3 content is 0.10 mol% or more and 2.00 mol% or less, The Na2O content is 1.00 mol% or more and 6.00 mol% or less, The CaO content is 0 mol% or more and 1.00 mol% or less, The total content of MgO, SrO, CaO and BaO (MgO+SrO+CaO+BaO) is 14.00 mol% or more.
3. The glass according to claim 1 or 2, wherein: The molar ratio of the Na2O content to the total content of Li2O, Na2O and K2O, Na2O / (Li2O+Na2O+K2O), is 0.350 or more.
4. The glass according to any one of claims 1 to 3, comprising Li2O.
5. The glass according to any one of claims 1 to 4, wherein The molar ratio of the Li2O content to the total content of Li2O, Na2O and K2O, Li2O / (Li2O+Na2O+K2O), is 0.600 or less.
6. The glass according to any one of claims 1 to 5, wherein The molar ratio of SiO2 content to Na2O content, SiO2 / Na2O, is 50.0 or less.
7. The glass according to any one of claims 1 to 6, wherein The molar ratio of the Na2O content to the MgO content, Na2O / MgO, exceeds 0.
080. 8 . The glass according to claim 1 , which has a specific elastic modulus of 35.0 MNm / kg or more. 9 . The glass according to claim 1 , which has a glass transition temperature of 700° C. or higher. 10 . A magnetic recording medium substrate, comprising the glass according to claim 1 . 11 . A magnetic recording medium comprising the magnetic recording medium substrate according to claim 10 and a magnetic recording layer. 12 . A glass spacer for a magnetic recording and reproducing device, comprising the glass according to claim 1 . 13 . A magnetic recording and reproducing device comprising at least one selected from the group consisting of the magnetic recording medium according to claim 10 and the glass spacer for a magnetic recording and reproducing device according to claim 12 .
Citation Information
Patent Citations
Glass substrate for information recording medium and magnetic information recording medium using the same
JP2002358626A
Glass for magnetic recording medium substrate, magnetic recording medium substrate and method for producing same, and magnetic recording medium
WO2011019010A1